Retrospective Accounts of Research Factors Associated with Significant and Not-So-Significant Research Outcomes - Daft, Richard L.; Griffin, Ricky W.; Yates, Valerie (Academy of Management Journal, 1987)
Three models with the potential to explain significant organizational research outcomes are described and evaluated. One model focuses on antecedent conditions, another on research processes, and the third on characteristics of research outcomes. Fifty-six organizational scholars reported about one of their significant and one of their not-so-significant research projects. Significance was operationally defined by ten attributes, including citations, awards, and positive responses from other researchers. The retrospective data identified several reported factors that occurred prior to and during research projects that were related to research outcomes. The model dealing with the research process itself differentiated significant from not-so-significant research better than either of the other models.